Konstruksi Pembelajaran Sejarah Islam Berbasis Teks Kajen dan Serat Cebolek dengan Pendekatan Ways of Knowing - Manggara Bagus Satriya Wijaya; Hermanu Joebagio; Sariyatun Sariyatun (UIN Sumatera Utara Medan, 2018)
Learning History in the Curriculum as a whole emphasizes the importance of collective memory so that inhibits the growth of critical reasoning in the Student. This review covers an alternative approach in teaching history subjects applied in senior high school. The use of the concept of critical questions and emancipatory models of